Recent Rubella infection among childbearing women in a tertiary hospital in Nigeria: a Seroepidemiological indication for vaccination need (2016)
Background: Congenital Rubella Infection can be prevented and future generation saved from disability by protecting women of reproductive age through vaccination. The study is aimed at determining serological evidence of recent rubella infection among women of childbearing age. Method: A cross sectional study was carried out among 285 women aged between 15 and 49 years. Enzyme immunoassay method was used to detect and quantify human IgM and IgG antibodies with avidity for Rubella virus in sera of participants. Socio-demographic characteristics of the subjects, along with recent history of fever, rash and adverse pregnancy outcome among others were obtained using a questionnaire. Statistical analysis was carried out using the program statistical package for social sciences (SPSS) version 16. Majority (78.3%) of the women recruited for the study were within 15-34 years age range. Of the 285 sera assayed for Rubella IgM antibodies, 23 (8.1%; 95% CI: 4.9%-11.3 %.) was IgM seropositive, while the remaining 262 (91.9%) were seronegative. A total of 7 (2.5%) of reproductive age women in Ilorin had a recent primary infection while 16 (5.6%) had a persistent Rubella infection or recent re-infection. In conclusion, there is need for vaccination of susceptible women of reproductive age in Ilorin as a large number of women have Rubella in their reproductive age.